2020
DOI: 10.1039/d0ra01163k
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise separation of poplar wood in oxalic acid/water and γ-valerolactone/water systems

Abstract: A combined treatment method of oxalic acid/H2O and γ-valerolactone/H2O can be used for efficient fractionation of hemicellulose, cellulose, and lignin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…It should be noted that not all nonchitinous content can be removed during the alkaline extraction process, given the occurrence of covalent cross-links between chitin and glucans . This characteristic differs significantly from lignocellulosic resources, where cellulose, lignin, and hemicellulose are physically bound and could be fractionated to yield nearly pure compounds . In this context, glucans are major structural polysaccharides of the fungal cell wall, constituting approximately 50–60 wt % of the wall, and a fraction of these glucans are alkali insoluble, so they will be present in the chitin extract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that not all nonchitinous content can be removed during the alkaline extraction process, given the occurrence of covalent cross-links between chitin and glucans . This characteristic differs significantly from lignocellulosic resources, where cellulose, lignin, and hemicellulose are physically bound and could be fractionated to yield nearly pure compounds . In this context, glucans are major structural polysaccharides of the fungal cell wall, constituting approximately 50–60 wt % of the wall, and a fraction of these glucans are alkali insoluble, so they will be present in the chitin extract.…”
Section: Resultsmentioning
confidence: 99%
“… 38 This characteristic differs significantly from lignocellulosic resources, where cellulose, lignin, and hemicellulose are physically bound and could be fractionated to yield nearly pure compounds. 39 In this context, glucans are major structural polysaccharides of the fungal cell wall, constituting approximately 50–60 wt % of the wall, and a fraction of these glucans are alkali insoluble, so they will be present in the chitin extract. These results highlight an increased purity of chitin isolated by the process employed here when compared to chitin extracted by simple alkali treatment at 65 °C and mechanical blending, which yields chitin/glucan ratios of 50/50 and 35/65 for Agaricus bisporus cap and stalk, respectively (note that mechanical blending resulted into a nanofibrillar material).…”
Section: Resultsmentioning
confidence: 99%
“…The released acetic acid concentration was 0.031 g/L when pretreated with 3% (w/v) oxalic acid. The acetyl groups on the side chain of hemicellulose are responsible for this phenomenon as they are mostly susceptible to be hydrolysed to acetic acid under more severe conditions 17 . It was reported that negligible amounts of formic acid, furfural and HMF were detected in oxalic acid-pretreated hyrolysate of PKC due to low severity employed (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study was conducted to assess the effectiveness of oxalic acid, formic acid, and citric acid for the hydrolysis of OPTB with xylose recoveries of 61.2%, 20.1%, and 12.9%, respectively. The superior performance of oxalic acid is attributed to its dicarboxylic structure, which is capable of selectively hydrolyzing hemicellulose to yield high monomer sugars and a solid with high enzymatic saccharification digestibility 15 17 . Therefore, it is expected that dilute oxalic acid will be effective for pretreatment of PKC with comparable levels of sugars to OPTB.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable pretreatment techni-ques offer unique opportunities to separate the chemical components of lignocellulose and enhance the saccharification of cellulose and hemicellulose. 7 It must be noted that the reactivity of cellulose, hemicellulose, and lignin derived from hardwood, softwood, and herbaceous plants varies due to the differences in the basic structural units. The search for efficient pretreatment methods suitable for various types of lignocelluloses is an urgent requirement for the development of biorefineries.…”
Section: ■ Introductionmentioning
confidence: 99%